Comparison of Nonimage- and Fluoroscopy-Guided Interlaminar Epidural Block: A Matched Paired Analysis in the Same Individuals. (1st April 2019) - Yoon, Syn-Hae; Park, Hanwool; Lee, Kunhee; Han, Haesol; Kang, Keum Nae; Lee, Gunn; Han, Yun A; Choi, Seong-Soo
Abstract : Background . Although fluoroscopic guidance is recommended highly for more accurate lumbar interlaminar epidural steroid injection (L-ESI), many physicians still use a nonimage-guided approach for L-ESIs. However, because of its associated risk of radiation and increased medical expense, the cost-effectiveness and safety of fluoroscopy-guided ESI have been called into question. The goal of this retrospective matched paired analysis in the same individuals was to assess the effectiveness and prevalence of complications of nonimage-guided L-ESI compared to those of fluoroscopy-guided L-ESI . Methods . Between 2015 and 2016, 94 patients who received both nonimage- and fluoroscopy-guided L-ESIs were analyzed retrospectively. The changes of the numeric rating scale (NRS) in pain intensity and functional outcome and the differences in the number of complications between blind and fluoroscopy-guided L-ESIs in the same individuals were evaluated by a matched paired analysis. Results . Of the 94 patients, the differences in NRS before and after the procedure were 1.29 (95% confidence interval (CI) = 0.94–1.65) for the nonimage-guided group and 1.64 (95% CI = 1.28–2.01) for the fluoroscopy-guided group (p = 0.16 ). More subjective functional improvement was observed in fluoroscopy-guided L-ESI (57, 60.6%) than in nonimage-guided L-ESI (47, 50.0%) without statistical significance (p = 0.16 ). Nine (9.6%) patients in the nonimage-guided group experienced complications related to the procedure overall compared to 4 (4.3%) in the fluoroscopy-guided group (p = 0.27 ). Conclusions . In this study, both blind and image-guided L-ESI techniques included similar extents of postprocedural outcomes and complications. Physicians should consider the risks associated with the two different techniques overall and develop ways to individualize the procedure to decrease the risk of complications and improve the positive outcomes of lumbar epidural steroid injections.